2004
DOI: 10.1002/mus.10559
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin‐induced neurotoxicity: Acute hyperexcitability and chronic neuropathy

Abstract: Oxaliplatin, a platinum-based chemotherapeutic agent, is effective in the treatment of solid tumors, particularly colorectal cancer. During and immediately following oxaliplatin infusion, patients may experience cold-induced paresthesias, throat and jaw tightness, and occasionally focal weakness. We assessed nerve conduction studies and findings on needle electromyography of patients with metastatic colorectal cancer before and during treatment with oxaliplatin. Twenty-two patients had follow-up studies within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
214
1
22

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(251 citation statements)
references
References 36 publications
12
214
1
22
Order By: Relevance
“…In particular, in patients developing acute neurotoxicity, a single electrical stimulus to the motor nerves produces a compound muscle action potential (CMAP) followed by repetitive discharges. At the same time, electromyography (EMG) studies show spontaneous high frequency discharges of motor unit multiplets [7,8]. Overall, these findings are consistent with those observed in neuromyotomia [9,10], an autoimmune disease caused by auto-antibodies against voltagegated potassium channels (VGKC).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In particular, in patients developing acute neurotoxicity, a single electrical stimulus to the motor nerves produces a compound muscle action potential (CMAP) followed by repetitive discharges. At the same time, electromyography (EMG) studies show spontaneous high frequency discharges of motor unit multiplets [7,8]. Overall, these findings are consistent with those observed in neuromyotomia [9,10], an autoimmune disease caused by auto-antibodies against voltagegated potassium channels (VGKC).…”
Section: Introductionsupporting
confidence: 75%
“…The first is probably related to an axonopathy due to the accumulation of platinum compounds within the dorsal root ganglia, the second to a transient impairment of ion channel function, but there is still no agreement about which channel is involved [6][7][8][11][12][13], neither about the possible correlation between acute and chronic neurotoxocity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, coldevoked hyperalgesia is a disabling condition in postherpetic neuralgia (Pappagallo et al, 2000) and in neuropathies caused by cancer chemotherapy, often limiting the maximal dosage of prescribed antitumoral drugs (Lehky et al, 2004). These effects have been generally interpreted as the result of an altered processing of the information provided by low-threshold cold receptors and nociceptors at spinal cord neurons (Wahren et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional nerve conduction studies provide information about compound action potential amplitude and conduction velocity, which are relatively non-specific measures and do not provide insight into ion channel function or resting membrane potential. Accordingly, prior studies have demonstrated that conventional nerve conduction studies are not sensitive to early change in chemotherapy-induced neurotoxicity [4][5][6] . In comparison, nerve excitability studies utilize threshold tracking techniques which have been developed to enable assessment of ion channels, pumps and exchangers in vivo in large myelinated human axons [7][8][9] .…”
mentioning
confidence: 99%